DAMPAK PROMOSI, DAYA TARIK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN GENERASI-Z DI SUSAN SPA BANDUNGAN - Andhyka Rizki Al Barkah; Amron, Amron (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to analyze the influence of promotional differentiation, attractiveness, and location on purchasing decisions at Susan Spa Bandungan. The population and sample of this study were done by purposive sampling technique on Susan Spa Bandungan consumers who were at least 17 years old and a maximum of 24 years old. In this study using a sample based on the formula N = (5 × number of indicators) = 5 × 18 = 90 respondents, but the researcher decided to use all the results obtained as many as 103 respondents to increase accuracy and anticipate invalid data. The research method applied is a quantitative approach and multiple linear regression analysis used to test the hypothesis with the IBM SPSS Statistic application. This study shows that promotion, attractiveness, and location have a positive and significant impact on purchasing decisions. These results are supported by data analysis which shows a strong relationship between these three factors and consumer decisions in choosing a product or service.